Remote Monitoring for Crop Security and Smart Irrigation using GSM Module - B., Sathish Kumar; Baskar, Radhika (International Journal of Psychosocial Rehabilitation, 2020)
In India, agriculture comes under the primary sector, which demonstrates most of the nation’s economy is depending on agriculture. Farmland depends on several factors such as water, temperature, humidity, security from intrusions, soil quality, disease identification, etc. Among several factors, the water system is one such factor where human consideration must be given more. The olden method of plant watering in a field is of two types: when to water the plants and how much water will be adequate for the plant. The proposed paper is mainly focused on three factors in agriculture. Firstly, smart irrigation system, real-time sensor data sent from the farmland and based on the data control of irrigation motor smartly using an Android application. Secondly, to provide security for the crops, a PIR (passive infrared) sensor is used to detect intrusions like animals and birds and immediately turn on the buzzer as well as the message sent to the user. Finally, remotely monitoring data like temperature, humidity, soil moisture, and PIR information is sent to the farmer based on his request. Now here comes the job of GSM (Global System Mobile) to send data to the user from the farmland. The user can see the information about farm land as a message in the Android application. As a result, user presence can be reduced, and precise measures of water given to the field provide security and monitor the field data. The proposed system is applicable to large farmlands and easily integrates with the conventional agriculture system.